ON THE ISSUE OF KAZAKHSTAN’S CONTRIBUTION TO NUCLEAR DISARMAMENT - Aubakirov Arthur (Theoretical Hypotheses and Empirical Results, 2023)
The article discusses the issues of peacekeeping activities of Kazakhstan and its invaluable contribution to promoting the idea of ​​renouncing nuclear weapon